Compound for organic luminescent material
By designing a new organic compound with a five-membered heterocyclic structure, the low luminescence efficiency problem caused by high exciton binding energy of organic luminescent materials is solved, and the hole transmission capacity is improved, which significantly improves the brightness of organic electroluminescent devices. Efficiency and lifespan.
Patent Information
- Application Number
- CN202510024844.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The exciton binding energy of existing organic luminescent materials is large, resulting in low luminescence efficiency and it is difficult for organic materials to obtain hole transport materials with high mobility.
A new organic compound with a five-membered heterocycle is designed as the parent core, and by introducing different groups, a new type of organic compound with suitable orbital energy and triplet energy is constructed as a second hole transport material or a phosphorescent host material.
It significantly improves the brightness efficiency and life of organic electroluminescent devices and improves the photoelectric performance.
Smart Images

Figure CN119462592A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic luminescent materials and relates to a compound used for organic luminescent materials. Background Art
[0002] Organic light-emitting diodes (OLEDs) offer advantages such as soft light emission, fast response, rich color, and wide viewing angles. The operating principle of OLEDs is that holes and electrons injected through electrodes enter the luminescent material through a transport layer. Under the influence of Coulomb forces, the holes and electrons combine to produce excitons, which then radiatively transition back to the ground state, emitting photons.
[0003] However, because the interaction between the conjugated molecules that make up organic light-emitting materials is weak van der Waals forces, the exciton binding energy is large, and the luminescence process is primarily driven by exciton behavior. Based on their spin state, excitons are divided into triplet excitons (75%) and singlet excitons (25%). Triplet excitons are transition-forbidden and have difficulty radiating and emitting photons, which limits the efficiency of OLED devices.
[0004] To address this issue, researchers have proposed phosphorescent OLED materials that utilize heavy metal atoms to enhance spin-orbit coupling, breaking the triplet spin prohibition and achieving room-temperature phosphorescent luminescence. This breakthrough surpasses the previous theoretical limit of 25% for the internal quantum efficiency (IQE) of fluorescent OLEDs. To maximize the performance of phosphorescent materials, they need to be doped into host materials to reduce the quenching effect of the luminescent material itself, thereby achieving higher device performance. Phosphorescent materials inherently have high triplet state energy. As the host of a phosphorescent material, its energy must be greater than that of the luminescent material; otherwise, energy backflow is likely to occur, reducing luminous efficiency. Phosphorescent host materials have developed rapidly in recent years, but host materials with high triplet states and high stability have always been a hot topic in the industry.
[0005] Furthermore, OLEDs still face numerous challenges. The conductivity of organic molecules is determined by two factors: first, intramolecular carrier transport originates from conjugated π bonds, where the pp electron clouds overlap to form bonding orbitals (HOMO energy levels) and anti-bonding orbitals (LUMO energy levels). The bonding orbitals have greater delocalization, which facilitates hole transport at the HOMO energy level. Second, inter-molecular transport primarily occurs through a hopping model, relying on the overlap of frontier molecular orbital electron clouds of adjacent molecules. Because bonding orbitals are highly delocalized, the electron clouds overlap more effectively, which also facilitates hole transport in organic materials. High mobility is difficult to achieve with organic materials, and the development of high-performance hole transport materials has long been a research goal for many researchers in the field.
[0006] Therefore, in the field of organic electroluminescent material technology, it is very important to construct a new compound that can not only enhance the stability of organic electroluminescent materials but also improve the photoelectric performance of organic electroluminescent devices. Summary of the Invention
[0007] In view of this, the object of the present invention is to provide a compound for organic light-emitting materials. The present invention uses a xanthene five-membered heterocycle as the parent core, introduces different groups at specific positions, and effectively improves the carrier migration ability by connecting electron-donating groups or electron-withdrawing groups. The constructed new organic compound has suitable orbital energy levels and triplet energy. As a second hole transport material or phosphorescent host material, it can effectively improve the brightness efficiency and lifespan, and significantly improve the photoelectric performance of organic electroluminescent devices.
[0008] The structure of the xanthene five-membered heterocycle involved in the present invention is as follows: .
[0009] In a first aspect, the present invention provides a compound having a structure as shown in Formula 1, ; Wherein, T is selected from one of C and Si; Y is selected from one of O, S, C(R3)2, and NAr3; m and n are independently selected from any value of 0, 1, 2, 3, and 4; Ar1 and Ar2 are independently selected from one of a C6-C30 substituted or unsubstituted aryl group, a C3-C30 substituted or unsubstituted heteroaryl group containing a N or O heteroatom, and an arylamine group containing an aryl group or a heteroaryl group; R1 and R2 are independently selected from one of methyl and phenyl groups; when R1 and R2 are both benzene rings, they can be connected to form a fluorene ring.
[0010] Furthermore, in the compound provided by the present invention, the R3 is selected from one of methyl and phenyl; Ar3 in the NAr3 is selected from one of benzene, biphenyl and terphenyl; When m>1, the plurality of Ar1s are the same as or different from each other; when n>1, the plurality of Ar2s are the same as or different from each other; Any hydrogen atom in Ar1, Ar2, or NAr3 may be replaced by deuterium.
[0011] Furthermore, the compounds provided by the present invention have structures as shown in Formula 2 to Formula 7, .
[0012] Furthermore, in the compound provided by the present invention, the heteroaryl group is selected from any one of the following structures:
[0013]
[0014]
[0015]
[0016]
[0017] .
[0018] Furthermore, in the compound provided by the present invention, the aromatic amine group is selected from any one of the following structures:
[0019]
[0020]
[0021]
[0022] .
[0023] Furthermore, the compound provided by the present invention has the structure shown below:
[0024]
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048]
[0049]
[0050]
[0051]
[0052]
[0053]
[0054]
[0055]
[0056]
[0057]
[0058]
[0059]
[0060]
[0061]
[0062]
[0063]
[0064]
[0065]
[0066]
[0067]
[0068]
[0069]
[0070]
[0071]
[0072]
[0073]
[0074]
[0075]
[0076]
[0077]
[0078]
[0079]
[0080]
[0081]
[0082]
[0083]
[0084]
[0085] 。
[0086] Furthermore, in the compounds provided by the present invention, the intermediates for synthesizing the compounds are selected from any one of the following structures:
[0087]
[0088]
[0089]
[0090]
[0091] .
[0092] In a second aspect, the present invention provides use of the compound in an organic electroluminescent device or an organic electroluminescent apparatus.
[0093] In a third aspect, the present invention provides the use of the compound in preparing hole transport materials or phosphorescent host materials.
[0094] In a fourth aspect, the present invention provides an organic electroluminescent device comprising an anode layer, a cathode layer, and an organic thin film layer located between the anode layer and the cathode layer, wherein the organic thin film layer comprises a hole injection layer, a first hole transport layer, a second hole transport layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer, and the light-emitting layer contains the compound described in the present invention.
[0095] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: The present invention provides a compound, wherein a xanthene five-membered heterocyclic ring enhances the rigidity of a parent nucleus, connects different groups at specific positions, and is modified by electron-withdrawing or electron-donating groups to construct a compound with a specific structure having suitable HOMO / LUMO energy levels and relatively high triplet energy. When used as a phosphorescent host material, the compound ensures energy transfer between the host and the guest, and when used as a second hole transport material, the compound enhances carrier migration capability, both significantly improving the brightness efficiency and lifespan of the device. The compound is a novel organic OLED functional material with relatively promising development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0096] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0097] Figure 1 Schematic diagram of the structure of an organic electroluminescent element. Reference numeral 1 is the substrate, 2 is the anode layer, 3 is the hole injection layer, 4 is the first hole transport layer, 5 is the second hole transport layer, 6 is the light-emitting layer, 7 is the hole blocking layer, 8 is the electron transport layer, 9 is the electron injection layer, and 10 is the cathode layer. DETAILED DESCRIPTION
[0098] The technical solutions of the present invention are described below with reference to the following examples. However, the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified. The reagents and materials described are commercially available unless otherwise specified. The percentages in the following examples are percentages by mass unless otherwise specified.
[0099] The structure of the xanthene five-membered heterocycle involved in the present invention is as follows: .
[0100] Preparation Example This preparation example provides the synthesis methods of some intermediates and compounds. The synthesis methods of the remaining intermediates and compounds are similar and can be easily synthesized. The specific synthesis routes are shown below.
[0101] Synthesis of intermediate 1-a:
[0102]
[0103] Synthesis of intermediate 1-1: Under nitrogen protection, raw material 1 (224 g, 1 mol), raw material 2 (180 g, 1 mol), Pd(PPh3)4 (tetrakis(triphenylphosphine)palladium, 23 g, 20 mmol), K2CO3 (potassium carbonate, 276 g, 2 mol), TBAB (tetrabutylammonium bromide, 32.2 g, 0.1 mol), toluene (2000 mL), ethanol (1000 mL), and water (500 mL) were added to a three-necked flask. The mixture was heated to 76°C and stirred for 8 h, then cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate, passed through a silica gel column, and then purified by recrystallization from toluene to obtain 210 g of intermediate 1-1 with a yield of 75%.
[0104] Synthesis of Intermediate 1-2: Under nitrogen, add Intermediate 1-1 (140 g, 0.5 mol) and tetrahydrofuran (400 mL) to a three-necked flask. A 1.0 M solution of methylmagnesium bromide in tetrahydrofuran (1.0 M THF, 800 mL) was slowly added dropwise with stirring at 24°C. After the addition was complete, the temperature was raised to 50°C and the reaction was continued for 5 h. The reaction solution was cooled to room temperature and quenched with aqueous ammonium chloride. The pH was adjusted to 3 with dilute hydrochloric acid, and then extracted with 800 mL of dichloroethane. The mixture was stirred until uniform and washed repeatedly with water. The organic phase was dried over anhydrous magnesium sulfate, filtered, concentrated, and the solid was squeezed out with ethanol. Purification afforded 114.8 g of Intermediate 1-2 in an 82% yield.
[0105] Synthesis of Intermediate 1-3: Under nitrogen, intermediate 1-2 (70.0 g, 0.25 mol), methanesulfonic acid (48 g, 0.5 mol), and toluene (500 mL) were added to a three-necked flask and heated to 108°C for 3 h. The reaction solution was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate, filtered, concentrated, and purified by recrystallization from a toluene / ethanol mixture to obtain 52.4 g of intermediate 1-3 in 80% yield.
[0106] Synthesis of intermediate 1-4: Under nitrogen protection, intermediate 1-3 (52.4 g, 0.2 mol), methyl 5-chloro-2-hydroxybenzoate (37.2 g, 0.2 mol), cesium carbonate (130.3 g, 0.4 mol) and DMF solvent (300 mL) were added to the reaction flask in sequence and heated under reflux for 6 h. The system was then cooled to room temperature, the reaction solution was filtered, and the filtrate was added to 900 mL of water with stirring. A white precipitate was formed, which was filtered. The filter cake was washed with water and ethanol in sequence to obtain a crude product, which was then purified by recrystallization from a toluene / ethanol mixed solvent to obtain 62.5 g of intermediate 1-4 with a yield of 73%.
[0107] The synthesis of Intermediate 1-5 refers to the synthesis of Intermediate 1-2, except that Intermediate 1-1 is replaced by Intermediate 1-4.
[0108] The synthesis of intermediate 1-a refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 1-5.
[0109] Synthesis of intermediate 1-b:
[0110]
[0111] The synthesis of intermediate 1-6 refers to the synthesis of intermediate 1-1, except that raw material 1 is replaced by raw material 3.
[0112] The synthesis of Intermediate 1-7 was based on the synthesis of Intermediate 1-2, except that Intermediate 1-1 was replaced by Intermediate 1-6.
[0113] The synthesis of Intermediate 1-8 was based on the synthesis of Intermediate 1-3, except that Intermediate 1-2 was replaced by Intermediate 1-7.
[0114] The synthesis of intermediate 1-9 refers to the synthesis of intermediate 1-4, except that intermediate 1-3 and methyl 5-chloro-2-hydroxybenzoate are replaced by intermediate 1-8 and 2,6-dibromophenol.
[0115] Synthesis of Intermediate 1-b: Under nitrogen, intermediate 1-9 (114 g, 0.2 mol) and tetrahydrofuran (300 mL) were added to a three-necked flask. After stirring and dissolving, the mixture was cooled to -10°C and butyl lithium (250 mL, 0.4 mol, 1.6 M) was slowly added dropwise. After incubation for 1 hour, a solution of diphenyldichlorosilane in tetrahydrofuran (50.4 g, 0.2 mol, 200 mL of tetrahydrofuran) was added dropwise. The reaction was continued at room temperature for another hour, then naturally warmed to room temperature and continued for 2 hours. After completion of the reaction, the reaction was quenched with aqueous ammonium chloride solution, extracted with 500 mL of dichloroethane, and repeatedly washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate, filtered, concentrated, extruded with ethanol, and purified by recrystallization from a toluene / n-heptane mixture to obtain 84.3 g of intermediate 1-b in a 71% yield.
[0116] Synthesis of intermediate 1-c:
[0117] The synthesis of intermediate 1-10 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 and methylmagnesium bromide are replaced by intermediate 1-4 and phenylmagnesium bromide.
[0118] The synthesis of intermediate 1-c was based on the synthesis of intermediate 1-3, except that intermediate 1-2 was replaced by intermediate 1-10.
[0119] Synthesis of intermediate 1-d:
[0120]
[0121] The synthesis of intermediate 1-11 refers to the synthesis of intermediate 1-1, except that raw material 2 is replaced by methyl 5-chlorobenzoate-2-boronic acid pinacol ester.
[0122] The synthesis of Intermediate 1-12 was based on the synthesis of Intermediate 1-2, except that Intermediate 1-1 was replaced by Intermediate 1-11.
[0123] The synthesis of intermediate 1-13 refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 1-12.
[0124] The synthesis of intermediate 1-14 refers to the synthesis of intermediate 1-4, except that intermediate 1-3 and 5-chloro-2-hydroxybenzoic acid methyl ester are replaced by intermediate 1-13 and 2-hydroxybenzoic acid methyl ester.
[0125] The synthesis of Intermediate 1-15 was based on the synthesis of Intermediate 1-2, except that Intermediate 1-1 was replaced by Intermediate 1-14.
[0126] The synthesis of intermediate 1-d was based on the synthesis of intermediate 1-3, except that intermediate 1-2 was replaced by intermediate 1-15.
[0127] Synthesis of intermediate 2-a:
[0128]
[0129] The synthesis of intermediate 2-1 refers to the synthesis of intermediate 1-1, except that raw materials 1 and 2 are replaced by raw materials 4 and 2-fluorophenylboronic acid.
[0130] Synthesis of Intermediate 2-2: Under nitrogen, add Intermediate 2-1 (135 g, 0.5 mol) and dichloromethane (1500 mL) to a dry three-necked flask. Cool the reaction system to -5–0°C using an ice-salt bath. Add boron tribromide (495 g, 2 mol). Stir at room temperature for 6 h before quenching the reaction by pouring into ice water. The organic phase is washed with water until neutral, dried over anhydrous magnesium sulfate, filtered, concentrated, and purified on a silica gel column to obtain 107.5 g of Intermediate 2-2 in an 84% yield.
[0131] The synthesis of intermediate 2-3 refers to the synthesis of intermediate 1-4, except that intermediate 1-3 and methyl 5-chloro-2-hydroxybenzoate are replaced by intermediate 2-2.
[0132] The synthesis of intermediate 2-4 was based on the synthesis of intermediate 1-4, except that intermediate 1-3 was replaced by intermediate 2-3.
[0133] The synthesis of intermediate 2-5 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 2-4.
[0134] The synthesis of intermediate 2-a refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 2-5.
[0135] Synthesis of intermediate 2-b:
[0136] The synthesis of Intermediate 2-6 refers to the synthesis of Intermediate 1-10, except that Intermediate 1-4 is replaced by Intermediate 2-4.
[0137] The synthesis of intermediate 2-b refers to the synthesis of intermediate 1-c, except that intermediate 1-10 is replaced by intermediate 2-6.
[0138] Synthesis of intermediate 2-c:
[0139]
[0140] The synthesis of intermediate 2-7 refers to the synthesis of intermediate 1-1, except that raw materials 1 and 2 are replaced by raw materials 4 and 4-chloro-2-fluorophenylboronic acid.
[0141] The synthesis of Intermediate 2-8 was based on the synthesis of Intermediate 2-2, except that Intermediate 2-1 was replaced by Intermediate 2-7.
[0142] The synthesis of intermediate 2-9 refers to the synthesis of intermediate 1-4, except that intermediate 1-3 and methyl 5-chloro-2-hydroxybenzoate are replaced by intermediate 2-8.
[0143] The synthesis of Intermediate 2-10 was based on the synthesis of Intermediate 1-14, except that Intermediate 1-13 was replaced by Intermediate 2-9.
[0144] The synthesis of intermediate 2-11 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 2-10.
[0145] The synthesis of intermediate 2-c was based on the synthesis of intermediate 1-3, except that intermediate 1-2 was replaced by intermediate 2-11.
[0146] Synthesis of intermediate 3-a:
[0147]
[0148] The synthesis of intermediate 3-1 refers to the synthesis of intermediate 1-1, except that raw material 2 is replaced by 2-nitrophenylboronic acid.
[0149] Synthesis of Intermediate 3-2: Under nitrogen, intermediate 3-1 (80 g, 0.3 mol), PPh3 (triphenylphosphine, 157.2 g, 0.6 mol), and o-dichlorobenzene (300 mL) were added to a three-necked flask. The mixture was stirred and heated to 160°C for 18 h. After cooling the reaction solution to room temperature, n-heptane was added to precipitate the solid product. The solid product was filtered and then recrystallized from toluene to obtain 53.6 g of intermediate 3-2, a yield of 76%.
[0150] Synthesis of Intermediate 3-3: Under nitrogen, a three-necked flask was charged with Intermediate 3-2 (47 g, 0.2 mol), iodobenzene (40.8 g, 0.2 mol), Pd2(dba)3 (tris(dibenzylideneacetone)dipalladium, 1.8 g, 2 mmol), P(t-Bu)3 (tri-tert-butylphosphine, 0.8 g, 4 mmol), sodium tert-butoxide (38.4 g, 0.4 mol), and toluene (400 mL). The mixture was stirred and heated to 110°C under reflux for 2 h. After the reaction was complete, the mixture was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate and filtered. The filtrate was passed through a silica gel column. The column liquid was concentrated and recrystallized from a toluene / ethanol mixture to obtain 52.8 g of Intermediate 3-3 in 85% yield.
[0151] The synthesis of intermediate 3-4 was based on the synthesis of intermediate 1-4, except that intermediate 1-3 was replaced by intermediate 3-3.
[0152] The synthesis of intermediate 3-5 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 3-4.
[0153] The synthesis of intermediate 3-a refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 3-5.
[0154] Synthesis of intermediate 3-b:
[0155]
[0156] The synthesis of intermediate 3-6 refers to the synthesis of intermediate 1-14, except that intermediate 1-13 is replaced by starting material 1.
[0157] The synthesis of intermediate 3-7 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 3-6.
[0158] The synthesis of Intermediate 3-8 was based on the synthesis of Intermediate 1-3, except that Intermediate 1-2 was replaced by Intermediate 3-7.
[0159] The synthesis of intermediate 3-9 refers to the synthesis of intermediate 1-1, except that raw materials 1 and 2 are replaced by intermediate 3-8 and 2-nitrophenylboronic acid.
[0160] The synthesis of intermediate 3-b was based on the synthesis of intermediate 3-2, except that intermediate 3-1 was replaced by intermediate 3-9.
[0161] Synthesis of intermediate 3-c:
[0162]
[0163] The synthesis of intermediate 3-10 refers to the synthesis of intermediate 1-4, except that intermediate 1-3 is replaced by starting material 1.
[0164] The synthesis of intermediate 3-11 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 3-10.
[0165] The synthesis of intermediate 3-12 refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 3-11.
[0166] The synthesis of intermediate 3-13 refers to the synthesis of intermediate 1-1, except that raw materials 1 and 2 are replaced by intermediate 3-12 and 2-nitrophenylboronic acid.
[0167] The synthesis of intermediate 3-14 requires a reaction method determined by the characteristics of the Ar1 group. Intermediate 3-14 can be obtained using conventional Suzuki or Ullmann synthesis methods.
[0168] The synthesis of intermediate 3-c was based on the synthesis of intermediate 3-2, except that intermediate 3-1 was replaced by intermediate 3-14.
[0169] Synthesis of intermediate 4-a:
[0170]
[0171] Synthesis of intermediate 4-1: Under nitrogen protection, raw material 5 (161 g, 1 mol), NBS (N-bromosuccinimide, 178 g, 1 mol), and chloroform (600 mL) were added to a three-necked flask and stirred at room temperature for 3 h. The reaction solution was concentrated and recrystallized from ethanol to obtain 205.5 g of intermediate 4-1, with a yield of 86%.
[0172] The synthesis of intermediate 4-2 refers to the synthesis of intermediate 1-1, except that raw materials 1 and 2 are replaced by intermediate 4-1 and 2-methylthiophenylboronic acid.
[0173] Synthesis of intermediate 4-3: Under nitrogen protection, intermediate 4-2 (141.5 g, 0.5 mol), acetic anhydride (51 g, 0.5 mol), and pyridine (600 mL) were added to a three-necked flask, stirred and heated to 100°C for 2 h. The raw material was detected by TLC. After the reaction was complete, it was cooled to room temperature, concentrated, and recrystallized from ethanol to obtain 130.1 g of intermediate 4-3, with a yield of 80%.
[0174] Synthesis of intermediate 4-4: Under nitrogen protection, intermediate 4-3 (65 g, 0.2 mol), HBr (200 mL), and acetic acid (200 mL) were added to a three-necked flask, stirred, and heated to 100°C for reaction. The raw materials were detected by TLC. After the reaction was complete, it was cooled to room temperature and toluene (300 mL) was added. After thorough stirring, the mixture was repeatedly washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate and purified on a silica gel column to obtain 38.8 g of intermediate 4-4 with a yield of 77%.
[0175] The synthesis of intermediate 4-5 refers to the synthesis of intermediate 1-4, except that intermediate 1-3 is replaced by intermediate 4-4.
[0176] The synthesis of intermediate 4-6 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 4-5.
[0177] The synthesis of intermediate 4-a refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 4-6.
[0178] Synthesis of intermediate 4-b:
[0179]
[0180] The synthesis of intermediate 4-7 refers to the synthesis of intermediate 4-2, except that 2-methylthiophenylboronic acid is replaced by 4-chloro-2-methylthiophenylboronic acid.
[0181] The synthesis of Intermediate 4-8 was based on the synthesis of Intermediate 4-3, except that Intermediate 4-2 was replaced by Intermediate 4-7.
[0182] The synthesis of Intermediate 4-9 was based on the synthesis of Intermediate 4-4, except that Intermediate 4-3 was replaced by Intermediate 4-8.
[0183] The synthesis of Intermediate 4-10 was based on the synthesis of Intermediate 1-14, except that Intermediate 1-13 was replaced by Intermediate 4-9.
[0184] The synthesis of intermediate 4-11 refers to the synthesis of intermediate 1-2, except that intermediate 1-1 is replaced by intermediate 4-10.
[0185] The synthesis of intermediate 4-b refers to the synthesis of intermediate 1-3, except that intermediate 1-2 is replaced by intermediate 4-11.
[0186] Synthesis of compound 1-1:
[0187] Under nitrogen, intermediate 1-a (8.2 g, 0.02 mol), diphenylamine (3.4 g, 0.02 mol), Pd2(dba)3 (tris(dibenzylideneacetone)dipalladium, 0.18 g, 0.2 mmol), P(t-Bu)3 (tri-tert-butylphosphine, 0.08 g, 0.4 mmol), sodium tert-butoxide (7.7 g, 0.08 mol), and toluene (100 mL) were added to a three-necked flask. The mixture was stirred and heated to 110°C under reflux for 1.5 h. After the reaction was complete, the mixture was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate and filtered. The filtrate was passed through a silica gel column, concentrated, and then recrystallized from toluene to obtain 9.0 g of compound 1-1 in 83% yield. The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 543.2562 [M+H] + ; C 40 H 33 NO (%) calculated value: C, 88.3633; H, 6.1180; N, 2.5762; O, 2.9426; found value (%): C, 88.3691; H, 6.1120; N, 2.5737; O, 2.9452.
[0188] Synthesis of compound 1-28:
[0189] Under nitrogen, a three-necked flask was charged with intermediate 1-a (8.2 g, 0.02 mol), 3,5-diphenyltriazinephenylboronic acid (5.5 g, 0.02 mol), Pd(PPh3)4 (tetrakis(triphenylphosphine)palladium, 0.5 g, 0.4 mmol), K2CO3 (potassium carbonate, 8.3 g, 0.06 mol), TBAB (tetrabutylammonium bromide, 0.3 g, 1 mmol), toluene (80 mL), ethanol (40 mL), and water (20 mL). The mixture was heated to 76°C with stirring for 6 h, then cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous magnesium sulfate, passed through a silica gel column, and then recrystallized from THF to obtain 9.5 g of compound 1-28 in a 78% yield. The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 607.2624 [M+H] + ; C 43 H 33 Calculated value of N3O (%): C, 84.9802; H, 5.4732; N, 6.9141; O, 2.6325; Found value (%): C, 84.9882; H, 5.4633; N, 6.9114; O, 2.6371.
[0190] Synthesis of compound 2-11:
[0191] The synthesis of compound 2-11 was carried out by referring to the synthesis method of compound 1-1, except that intermediate 1-a and diphenylamine were replaced by intermediate 2-a and 4-anilinobiphenyl with a fully deuterated phenyl ring. The yield was 79%; the deuterium banding rate of the obtained sample was 85.6%, and the mass spectrometry results were: HR-MS (APCI): m / z 593.1259 [M+H] + .
[0192] Synthesis of compound 2-13:
[0193]
[0194] The synthesis of compound 2-13 was carried out according to the synthesis method of compound 1-1, except that intermediate 1-a and diphenylamine were replaced by intermediate 2-a and intermediate 3. The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 607.2147 [M+H] + ; C 43 H 29 Calculated value for O3N (%): C, 84.9869; H, 4.8102; N, 2.3049; O, 7.8980; Found (%): C, 84.9891; H, 4.8090; N, 2.3052; O, 7.8967.
[0195] Synthesis of compound 3-10:
[0196]
[0197] The synthesis of intermediate 1, intermediate 2 and compound 3-10 all referred to the synthesis method of compound 1-1, and the corresponding intermediate raw materials were selected for synthesis. The mass spectrometry results of the final obtained compound 3-10 were: HR-MS (APCI): m / z 835.3563 [M+H] + ; C 61 H 45 ON3 (%) calculated value: C, 87.6347; H, 5.4255; N, 5.0261; O, 1.9136; found value (%): C, 87.6391; H, 5.4202; N, 5.0252; O, 1.9155.
[0198] With reference to the synthesis methods of compounds 1-1 and 1-28, all compounds of the present invention can be synthesized. The only difference is that different parent intermediates and intermediates corresponding to the modifying groups need to be used to replace the products, and the mass amount of the intermediates is changed according to the molar amount. The replacement relationship between the parent intermediates and the intermediates corresponding to the modifying groups, reactants, and compounds is shown in Table 1.
[0199] Table 1 Replacement relationship between the core intermediates and the corresponding intermediates, reactants and compounds of the modified groups
[0200] The performance parameters (including HOMO energy level and LUMO energy level, triplet energy T1, Eg) of the compound synthesized by the present invention and the existing OLED materials HT2 (Comparative Example 1) and H1 (Comparative Example 2) were measured. The results are shown in Table 2.
[0201] Table 2 Performance parameter measurement results of compounds and existing materials
[0202] Note: The highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO), and the triplet energy T1 are calculated using Gaussian 09 software using the B3LYP hybrid functional and basis set 6-31g(d); Eg = the absolute value of HOMO - LUMO.
[0203] As shown in Table 2, the compounds provided by the present invention have suitable triplet energies and HOMO / LUMO energy levels, which are beneficial to carrier transport and energy transfer in OLED devices. The compounds of the present invention are suitable for use as second hole transport materials or phosphorescent host materials.
[0204] Taking some compounds provided by the present invention as examples, they are respectively applied as the second hole transport material or the main material of the light-emitting layer in an organic electroluminescent device to verify the excellent effects achieved.
[0205] Example 1 This embodiment provides an organic electroluminescent device, the structure of which is as follows: Figure 1 As shown, it includes a substrate 1, an anode layer 2, a hole injection layer 3, a first hole transport layer 4, a second hole transport layer 5, a light-emitting layer 6, a hole blocking layer 7, an electron transport layer 8, an electron injection layer 9 and a cathode layer 10 stacked in sequence.
[0206] Among them, the substrate 1 is a glass substrate with a thickness of 0.7 mm, the material of the anode layer 2 is indium tin oxide (ITO) with a high work function, the material of the hole injection layer 3 is HAT-CN with a thickness of 5 nm; the material of the first hole transport layer 4 is HT1 with a thickness of 60 nm; the material of the second hole transport layer 5 is compound 1-1 with a thickness of 10 nm; the light-emitting layer 6 uses GD01 as the light-emitting material and CBP as the main material, with a doping mass ratio of 6% and a thickness of 30 nm; the material of the hole blocking layer 7 is HB1 with a thickness of 10 nm; the material of the electron transport layer 8 is ET1 with a thickness of 35 nm; the material of the electron injection layer 9 is Liq with a thickness of 2 nm; the material of the cathode layer is Al with a thickness of 100 nm.
[0207] The basic material structures used in each functional layer of the device are as follows:
[0208]
[0209]
[0210] The specific preparation steps of the above-mentioned organic electroluminescent device are as follows: (1) Clean the ITO anode layer on the transparent glass or plastic substrate by ultrasonic cleaning with deionized water, acetone, and ethanol for 20 minutes each, and then perform plasma treatment in an oxygen atmosphere for 5 minutes; (2) On the ITO anode layer, the hole injection layer material HAT-CN is deposited by vacuum evaporation with a thickness of 5 nm. This layer serves as the hole injection layer. (3) Vacuum evaporation of a hole transport material HT1 to a thickness of 60 nm on the hole injection layer, which serves as the first hole transport layer; (4) Hole transport material compound 1-1 was deposited on the first hole transport layer HT1 by vacuum evaporation to a thickness of 15 nm. This layer served as the second hole transport layer. (5) On the second hole transport layer, a light-emitting layer was co-deposited by vacuum evaporation, using CBP as the host material and GD01 as the doping material, with a doping mass ratio of 6% and a thickness of 30 nm; (6) On top of the light-emitting layer, a hole blocking material HB1 is deposited by vacuum evaporation with a thickness of 10 nm. This layer serves as a hole blocking layer. (7) On the hole blocking layer, the electron transport material ET1 is evaporated by vacuum evaporation with a thickness of 35 nm. This layer serves as the electron transport layer; (8) On the electron transport layer, the electron injection material Liq is evaporated by vacuum evaporation with a thickness of 2 nm. This layer serves as the electron injection layer; (9) On the electron injection layer, cathode Al is evaporated by vacuum evaporation with a thickness of 100 nm. This layer is used as a cathode conductive electrode and is the cathode layer.
[0211] Examples 2 to 25 The preparation process of Examples 2 to 25 is the same as that of Example 1, except that the second hole transport material uses compound 1-8, compound 1-13, compound 1-41, compound 2-2, compound 2-6, compound 2-11, compound 2-13, compound 2-34, compound 2-39, compound 3-7, compound 3-11, compound 3-17, compound 3-20, compound 3-22, compound 3-24, compound 3-35, compound 3-38, compound 3-46, compound 3-54, compound 4-1, compound 4-6, compound 4-34, compound 4-43, and compound 4-49 synthesized in the preparation example of the present invention instead of compound 1-1.
[0212] Comparative Example 1 Comparative Example 1 is the same as Example 1, except that the second hole transport material uses compound HT2 instead of compound 1-1.
[0213] Each group of organic electroluminescent devices was connected to the cathode and anode using a known driving circuit. The voltage-efficiency-current density relationship of the OLED devices was tested using a standard method using a Keithley 2400 power supply and a PR670 photometer. The device life was tested using a constant current method with a constant current density of 10 mA / cm 2 The time it takes for the brightness to decay to 95% of the initial brightness is the device’s LT95 lifespan. The results are shown in Table 3.
[0214] Table 3 Comparison of performance results of organic electroluminescent devices in each group
[0215] As can be seen from Table 3, the compounds provided by the present invention are applied as hole transport materials in OLED green light devices, and the performance is improved. For example, compared with HT2 in the comparative example, compound 2-6 in Example 6 as a hole transport material has improved energy transmission capacity, luminous efficiency and service life are significantly improved, with brightness efficiency increased by 42% and service life increased by 98%.
[0216] Example 26 The substrate 1 is a glass substrate with a thickness of 0.7 mm. The material of the anode layer 2 is indium tin oxide (ITO) with a high work function. The material of the hole injection layer 3 is HAT-CN with a thickness of 5 nm. The material of the first hole transport layer 4 is HT1 with a thickness of 60 nm. The material of the second hole transport layer 5 is TCTA with a thickness of 10 nm. The light-emitting layer 6 uses RD01 as the light-emitting material and the compound 1-20 of the present invention as the main material with a doping mass ratio of 6% and a thickness of 30 nm. The material of the hole blocking layer 7 is HB1 with a thickness of 10 nm. The material of the electron transport layer 8 is ET1 with a thickness of 35 nm. The material of the electron injection layer 9 is Liq with a thickness of 2 nm. The material of the cathode layer is Al with a thickness of 100 nm.
[0217] The specific preparation steps are as follows: (1) Clean the ITO anode layer on the transparent glass or plastic substrate by ultrasonic cleaning with deionized water, acetone, and ethanol for 20 minutes each, and then perform plasma treatment in an oxygen atmosphere for 5 minutes; (2) On the ITO anode layer, the hole injection layer material HAT-CN is deposited by vacuum evaporation with a thickness of 5 nm. This layer serves as the hole injection layer. (3) Vacuum evaporation of a hole transport material HT1 to a thickness of 60 nm on the hole injection layer, which serves as the first hole transport layer; (4) A hole transport material TCTA is deposited on the first hole transport layer HT1 by vacuum evaporation with a thickness of 15 nm. This layer serves as the second hole transport layer. (5) On the second hole transport layer, a light-emitting layer was co-deposited by vacuum evaporation, using compound 1-20 as the host material and RD01 as the doping material, with a doping mass ratio of 6% and a thickness of 30 nm; (6) On top of the light-emitting layer, a hole blocking material HB1 is deposited by vacuum evaporation with a thickness of 10 nm. This layer serves as a hole blocking layer. (7) On the hole blocking layer, the electron transport material ET1 is evaporated by vacuum evaporation with a thickness of 35 nm. This layer serves as the electron transport layer; (8) On the electron transport layer, the electron injection material Liq is evaporated by vacuum evaporation with a thickness of 2 nm. This layer serves as the electron injection layer; (9) On the electron injection layer, cathode Al is evaporated by vacuum evaporation with a thickness of 100 nm. This layer is used as a cathode conductive electrode and is the cathode layer.
[0218] Examples 27-38 The preparation process of Examples 27 to 38 is the same as that of Example 26, except that the main material of the light-emitting layer uses Compound 1-24, Compound 1-26, Compound 1-28, Compound 1-32, Compound 1-36, Compound 2-28, Compound 2-36, Compound 2-37, Compound 2-44, Compound 4-26, Compound 4-32, and Compound 4-36 synthesized in the preparation example of the present invention instead of Compound 1-20.
[0219] Comparative Example 2 The preparation process of Comparative Example 2 is the same as that of Example 26, except that the main material of the light-emitting layer is replaced by Compound H1 synthesized in the preparation example of the present invention instead of Compound 1-20.
[0220] Each group of organic electroluminescent devices was connected to the cathode and anode using a known driving circuit. The voltage-efficiency-current density relationship of the OLED devices was tested using a standard method using a Keithley 2400 power supply and a PR670 photometer. The device life was tested using a constant current method with a constant current density of 10 mA / cm 2 The time it takes for the brightness to decay to 95% of the initial brightness is the device’s LT95 lifespan. The results are shown in Table 4.
[0221] Table 4 Comparison of performance results of organic electroluminescent devices in each group
[0222] As shown in Table 4, the compounds provided by the present invention are applied to OLED red light devices as the main materials of the light-emitting layer, and the performance is also improved. For example, when compound 2-37 in Example 34 is used as the main material, compared with H1 in the comparative example, the luminous efficiency and service life are significantly improved, the brightness efficiency is increased by 50%, and the service life is increased by 83%. When the compounds of other embodiments are used as the main materials, the luminous efficiency and life are significantly improved. The compounds described in the present invention can all be used as the main materials of the light-emitting layer. In order to achieve better luminous effects, compounds 3-1 to 3-70 are more suitable as hole transport materials. It can be seen that the efficiency and life of the device are well performed by selecting the compounds of the present invention, and the synthesis process of the material is simple. It has great application value in the application of OLED devices and has good industrialization prospects.
[0223] As described above, the basic principles, main features and advantages of the present invention are well described. The above embodiments and descriptions are merely descriptions of preferred embodiments of the present invention, and the present invention is not limited to the above embodiments. Various changes and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit and scope of the present invention should fall within the scope of protection determined by the present invention.
Claims
1. A compound, characterized in that Having a structure as shown in Formula 1, ; Wherein, T is selected from one of C and Si; Y is selected from one of O, S, C(R3)2, and NAr3; m and n are independently selected from any value of 0, 1, 2, 3, and 4; Ar1 and Ar2 are independently selected from one of a C6-C30 substituted or unsubstituted aryl group, a C3-C30 substituted or unsubstituted heteroaryl group containing a N or O heteroatom, and an arylamine group containing an aryl group or a heteroaryl group; R1 and R2 are independently selected from a methyl group and a phenyl group; when R1 and R2 are both benzene rings, they can be connected to form a fluorene ring.
2. The compound according to claim 1, characterized in that The R3 is selected from one of methyl and phenyl; Ar3 in the NAr3 is selected from one of benzene, biphenyl and terphenyl; When m>1, the plurality of Ar1 are the same or different from each other; when n>1, the plurality of Ar2 are the same or different from each other; Ar1, Ar 2、 Any hydrogen atom in NAr3 can be replaced by deuterium.
3. The compound according to claim 1, characterized in that The compound has a structure as shown in Formula 2 to Formula 7, 。 4. The compound according to claim 1, characterized in that The heteroaryl group is selected from any one of the following structures, 。 5. The compound according to claim 1, characterized in that The aromatic amine group is selected from any one of the following structures, 。 6. The compound according to claim 1, characterized in that Has the following structure, 。 7. The compound according to claim 6, characterized in that The intermediate for synthesizing the compound is selected from any one of the following structures, 。 8. Use of the compound according to any one of claims 1 to 7 in an organic electroluminescent device or an organic electroluminescent apparatus.
9. Use of the compound according to any one of claims 1 to 7 in the preparation of hole transport materials or phosphorescent host materials.
10. An organic electroluminescent device, comprising an anode layer, a cathode layer and an organic thin film layer located between the anode layer and the cathode layer, wherein the organic thin film layer comprises a hole injection layer, a first hole transport layer, a second hole transport layer, a light emitting layer, a hole blocking layer, an electron transport layer and an electron injection layer, characterized in that: The light-emitting layer contains the compound according to any one of claims 1 to 7.
Citation Information
Patent Citations
Compound using spirobibenzocycloheptene fluorene as core, and applications in organic electroluminescent devices
CN110655471A
Compound and application thereof in organic electroluminescent device
CN118652227A
Condensed ring compound for organic electroluminescent device
CN119219657A
Fused phenylquinazolines bridged with a heteroatom
EP3466954A1
Bedclothes Automatic packaging machine
KR102334737B1
Cited By
Xanthene fused ring compound for organic light-emitting material and application of xanthene fused ring compound
CN120004843A